Сучасне розподілене виробництво (мануфактура) як важлива частина української національно укоріненої промисловості майбутнього - Amosha, Oleksandr I.; Amosha, Olena O. (Institute of Industrial Economics of NAS of Ukraine, 2024)
The purpose of this paper is to propose a variant for the development of a part of the national industry, which would be free from the problems of large investments and threats of unprofitability against the background of innovations.Before the full-scale war, which began in 2022, Ukrainian industry was an offspring and a powerful part of the Soviet heavy industry, mainly of the third technological order. Now, the enterprises that were powerful generators of the national economy GDP are to a greater extent located in the temporarily occupied or front-line territory. Industrial regions suffered significant damage to the production base and infrastructure facilities. The post-war restoration of the domestic industry requires large capital investments, which the national economy is not capable of. In addition, there is a limitation on the duration of investment projects due to the rapid development of modern technologies. According to experts, any project whose implementation exceeds 3 years is risky. In addition, there is a Marxian tendency of the rate of profit to decrease, due to a change in the capital structure, in particular, a decrease in labor expenses. Modern processes of mechanization of production, increase of innovative components (computerization, Internet of things, digitalization, etc.) increase the risks of unprofitability. The authors give an example of the closure of coal mining enterprises in European countries against the background of scientific and technical progress.At the same time, based on the analysis of literary sources, the trend of the spread of the DIY 4.0 phenomenon (from Do It Yourself) was revealed – the use of the most modern technological elements for the manufacture of products designed to meet the manufacturers' own needs. Especially in the USA, the Maker Movement, which is a new culture of industrial activity, is developing.The article substantiates that the technological base of DIY 4.0 and the culture of the Maker Movement are the foundation of the new distributed manufacturing, free from the "curse" of mass investment and unprofitable innovation. It is distributed manufacturing that is able to fundamentally change the quality picture and structure of industry, to ensure the national rooting of industrial production.